Application of EdgeFlow mobile edge computing in Internet of things - Shuchang CONG; Chao YAO; Chao YAO; Pengfei WANG; Zijie ZHENG (物联网学报)
In order to meet the requirements of higher computing speed,lower communication delay and higher access density in the future Internet of things,a computational framework of EdgeFlow for mobile edge computing and a task unloading algorithm considering blocking and non-blocking state were proposed.The simulation experiments on the universal software radio platform show that the computational efficiency can be improved significantly and the communication delay can be reduced by EdgeFlow.It points out a new development direction,lays a theoretical and practical foundation for solving the problem of higher computational requirements of the Internet of things.And it will be widely used in the Internet of things scenarios.